Foliar Application of Boron Nanoencapsulated in Almond Trees Allows B Movement Within Tree and Implements Water Uptake and Transport Involving Aquaporins - Rios, Juan J.; Lopez-Zaplana, Alvaro; Bárzana, Gloria; Martinez-Alonso, Alberto; Carvajal, Micaela (Frontiers in Plant Science, 2021)
Nanotechnology brings to agriculture new forms of fertilizer applications, which could be used to reduce environmental contamination and increase efficiency. In this study, foliar fertilization with nanoencapsulated boron (B) was studied in comparison to an ionic B (non-encapsulated) application in young B-deficient almond trees grown under a controlled environment. B movement within the plant in relation to the leaf gas exchange, water relations parameters, and root hydraulic conductance was measured. Also, the expression of aquaporins (AQPs) [plasma membrane intrinsic protein (PIP) and tonoplast intrinsic protein (TIP)] was studied in relation to water uptake and transport parameters to establish the effectiveness of the different B treatments. The obtained results were associated with a high concentration of observed B with nanoencapsulated B, provided by the higher permeability of carrier nanovesicles, which allowed B to reach the cell wall more efficiently. The increases in water uptake and transport obtained in these plants could be related to the role that this element played in the cell wall and the relationship that it could have in the regulation of the expression of AQPs and their involvement in water relations. Also, an increase in the expression of PIPs (mainly PIP2.2) to the applied nanoencapsulated B could be related to the need for B and water transport, and fine regulation of TIP1.1 in relation to B concentration in tissues provides an important feature in the remobilization of B within the cell.